Animal Assisted Therapy (AAT) in children with autism spectrum disorder attended by the Psychosocial Care Center (Research, Society and Development, 2020)
Animal Assisted Therapy (AAT) aims to introduce an animal to na individual or a group with the purpose of promoting physical, mental and emotional health. This practice, which has become increasingly common in the world, has grown in Brazil. The present study aimed to evaluate the use of AAT assisting children with autism. Patients (n = 5)participating in the study were under medical care at the Clinical Service Center and Institute of Psychology (CAPsi) of Uberlandia, Minas Gerais, Brazil. Ten chicks, of approximately one week old, were used in the AAT sessions.  AAT meetings were held once a week, for one hour, during four months. Only one of the children who participated in the activity was not interested in the animals. The remaining four children demonstrated affection towards the chicks, and an overall improvement in socialization behaviors and quality of life of families participating in the study were observed. These results support the idea that AAT improves social interactions and behaviors and leads to improvements in household relationships.